Macmillan Studies in Economics / Relative Income Shares - King John; Regan Philip (Macmillan Press Ltd, 1976)
An introductory examination to current theories and empirical evidence concerning the distribution of national income between labor and property. Acknowledgements, Introduction, A Survey of the Evidence, Cyclical Movement in Relative Shares, Relative Shares in the Long Run, The Recent ''Profits squeeze'', Conclusion, Marginal Productivity Theory, Early Approaches, Modern Developments, Aggregation, Marginal Productivity: The Econometrics, The Cobb-Douglas Production Function, Empirical Estimates of the Cobb-Douglas Function, The C.E.S. Production Function, ''Monopoly'' and Relative Shares, Neo-Keynesian Theories, Unions and Relative Shares, Conclusion.